Study on thermal characteristics of deep groove ball bearing based on Green's Function and COMSOL. Issue 1 (February 2021) - Zhang, Kai; Hu, Hanping; Liu, Xiaojie
Abstract: Thermal characteristics seriously affect the performance of bearing, which analyzing the temperature field of bearing is inevitable. This paper presents a better solution based on Green's Function. It is more efficient and accurate than the integral transform method provided in current literature. The finite element method (FEM) with COMSOL is applied to simulate in the three-dimensional model. By comparing analytical solution and FEM, the tendency of temperature is reasonable. And the maximum temperature locates at the roller is 41.2476 °C . Beside, little difference in temperature between inner and outer raceway and the former is little high. Moreover, heat flux only transfers from rollers to raceway, which causes thermal load on the contact region. According to the analytical method, deep groove needs equivalent treatment to reduce error. Then 40.7995°C obtained by Green's Function and 40.8592°C obtained by COMSOL in the same position on inner raceway. This paper mainly provides an advantage analytical method to verify the temperature field in deep groove ball bearing, and it is valuable for studying thermal reliability of bearing.